2023
DOI: 10.3390/v15030690
|View full text |Cite
|
Sign up to set email alerts
|

Packaging and Uncoating of CRISPR/Cas Ribonucleoproteins for Efficient Gene Editing with Viral and Non-Viral Extracellular Nanoparticles

Abstract: Rapid progress in gene editing based on clustered regularly interspaced short palindromic repeats/CRISPR-associated protein (CRISPR/Cas) has revolutionized functional genomic studies and genetic disease correction. While numerous gene editing applications have been easily adapted by experimental science, the clinical utility of CRISPR/Cas remains very limited due to difficulty in delivery to primary cells and possible off-target effects. The use of CRISPR in the form of a ribonucleoprotein (RNP) complex substa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…A limitation of this approach was that not every cell of egg appeared positive for the RNPs. To optimize this, alternative transfection methods such as lipid nanoparticles (97) and other methods (82,(98)(99)(100)(101)(102) could be tested. Alternatively, one could envisage to use larval stages such as sporocysts as editing templates to enhance cell-transfection efficiency (61).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this approach was that not every cell of egg appeared positive for the RNPs. To optimize this, alternative transfection methods such as lipid nanoparticles (97) and other methods (82,(98)(99)(100)(101)(102) could be tested. Alternatively, one could envisage to use larval stages such as sporocysts as editing templates to enhance cell-transfection efficiency (61).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of research on infectious diseases, exosome-based CRISPR/Cas9 delivery has been suggested as a potential strategy for producing innovative therapies for viral infections including HIV and hepatitis B. For instance, a 2018 study discovered that exosomes containing CRISPR/Cas9 may target and harm HIV proviral DNA in vitro , decreasing the virus’ ability to produce genetic material ( Dubey et al, 2022 ; Mazurov et al, 2023 ). Like this, exosome-based CRISPR/Cas9 delivery was shown to effectively target the hepatitis B virus (HBV) genome in vitro and in vivo , leading to a reduction in viral replication and gene expression ( Martinez et al, 2022 ).…”
Section: Need For Biomaterials: Advantages Over Other Delivery Methodsmentioning
confidence: 99%